Evaluation of local maize (Zea mays L.) varieties from Burkina Faso as source of tolerance to drought - Olaoye, G.; Menkir, A.; Ajala, S.O.; Jacob, S. (2009)
To evaluate local maize varieties from Burkina Faso under moisture deficiency to identify suitable genotypes to serve as sources of drought tolerance alleles for incorporation into improved cultivars. Methodology and results: Fourteen local maize varieties from Burkina Faso and a hybrid check were evaluated under well-watered condition and drought stress imposed by withdrawing irrigation from 23 days before 50% anthesis until harvest at Ikenne in Nigeria in 1999 and 2000. Moisture deficiency significantly (P<0.05) reduced the number of ears per plant by 22% and grain yield by 53%. Three local varieties (Bondokuy-1, Dogona-1 and Douana-1) had grain yields that were either comparable to or higher than that of the hybrid check under moisture deficit. Relative ranking of genotypes for grain yield under well-watered condition was different from those under moisture deficiency. Two major clusters were formed for genotypes tested under each irrigation treatment, with entries in cluster 2 combining high grain yield with shorter anthesis-silking interval and lower leaf senescence rating. Some local varieties exhibited comparable performance to the hybrid check, suggesting the possibility that genes for high grain yield and other desirable agronomic attributes may have been introgressed into the local maize varieties through pollen transfer from adjacent improved varieties that have been cultivated in the region and thus increasing their utility values. Conclusion and application of findings: Three genotypes, i.e. Bondokuy-1, Dogona-1 and Douana-1 had high grain yields under both well watered and moisture deficiency conditions. These accessions could serve as potential sources of favorable alleles for developing high yielding varieties adapted to areas affected by drought in West and Central Africa.